Factors leading to continuance intention to use big-bikes in Thailand - Athipon Mathawikul; Chonlatis Darawong (Cogent Business & Management, 2023)
The big-bike market has been experiencing steady growth, particularly over the last five years. This upward trend is projected to persist in the future as these products effectively cater to consumers' desires for convenience, image, and high performance. This study examines the critical factors affecting big-bike marketing in Thailand with a focus on the continuance of intention to use the product. Using a mixed-method approach, this study investigates the key factors and indicators in Thailand's big-bike (motorcycle) marketing strategy concerning customers' intention to continue using the product. Four hundred respondents participated in a quantitative survey, and in-depth interviews are conducted for qualitative data collection. Three key factors and 11 key indicators in big-bike marketing were identified. Results reveal customer value (satisfaction) improves brand perception (loyalty), influencing consumers' intention to continue using or purchasing the product; product value directly influences this intention. The implications of the qualitative findings suggest that advertisers of big-bikes in Thailand should emphasise individualism, the sensation of escapism, heightened self-esteem, and the exhilarating rush experienced during rides. Manufacturers should prioritise the creation of a distinctive and recognisable design while emphasising the attributes of reliability and safety. These findings can guide individuals promoting the big-bike industry in Thailand.
Keywords: 650; big-bike products; brand perception; continuance intention; customer value; key factors; product value; Thailand